2010
DOI: 10.1016/j.jcrs.2010.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient satisfaction with outcomes of and ophthalmic care for cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…In studies similar to ours, AUCs are not provided for models, and none of the models explored predictors for satisfaction with the ability to perform specific activities after cataract extraction. Another strength is that patients in our study completed quality‐of‐life and satisfaction questionnaires 3 months after surgery, while most similar studies measured patient satisfaction just 1 month after surgery . The extended follow‐up could better reflect a patient's ultimate visual situation as it occurs well past the visit 6 weeks after the intervention when VA is assessed and the patient's glasses are re‐accommodated to the new VA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies similar to ours, AUCs are not provided for models, and none of the models explored predictors for satisfaction with the ability to perform specific activities after cataract extraction. Another strength is that patients in our study completed quality‐of‐life and satisfaction questionnaires 3 months after surgery, while most similar studies measured patient satisfaction just 1 month after surgery . The extended follow‐up could better reflect a patient's ultimate visual situation as it occurs well past the visit 6 weeks after the intervention when VA is assessed and the patient's glasses are re‐accommodated to the new VA.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐reported outcomes (PROs) provide the patient's perspective about the success or failure of an intervention. They can help clinicians understand the effects of disease and treatment on symptoms, functioning and other outcomes . The use of patient‐reported outcomes (PROs) as a complement to classical clinical outcomes is increasing in elective surgery and other domains.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative visits, ocular surface discomfort and inflammation are less frequent after phacoemulsification than after glaucoma filtration surgery [36]. Unsurprisingly, numerous studies [37] have demonstrated greater patient satisfaction following phacoemulsification surgery. Coupled with reduced expense, an argument [30 && ] develops for a procedure with shorter recovery, faster visual rehabilitation, less onerous follow-up and reduced risk.…”
Section: Cataract Surgery Versus Clear Lens Phacoemulsificationmentioning
confidence: 99%
“…147 On the other hand, it must also be borne in mind that patient expectations are one of the primary factors which determine satisfaction. 148 Nowadays, these expectations are generally too high [149][150][151] and sometimes unrealistic. Given that VA increase (Snellen) and visual function improvement (VF-14) do not necessarily correlate with patient satisfaction, it is necessary to address unrealistic expectations by providing sufficient previous information and addressing it in writing.…”
Section: Variability and Health Services Qualitymentioning
confidence: 99%